Flavonone from Callus Culture of Pomelo (Citrus grandis) - Azlinda, A.; Zarina, Zakaria, Dr.; Ku Syahidah, Ku Ismail; Nor Alina, N. (University Malaysia Perlis (UniMAP), 2011)
Organized by University Malaysia Perlis (UniMAP), 12th - 13th Disember 2009 at Putra World Trade Centre (PWTC), Kuala Lumpur, Malaysia.